Comparative study on open appendicectomy versus laparoscopic appendicectomy in a tertiary care centre - S., Naraintran; David S., Sandeep Kumar; K., Raveendran; B. K., Eashwara Pilla (International Surgery Journal, 2018)
Background: Appendicectomy is one of the most common procedure in general surgery, accounts for approximately 1% of all surgical operation. Laparoscopic appendicectomy are likely to have less postoperative pain, early discharge, decreased wound infection, better cosmesis and also early return to routine work. Laparoscopic procedure for appendicectomy is compared with open surgical technique with respect to duration of surgery, post operative pain, duration of analgesic, post operative complications, post operative length of hospital stay and return to routine work. Methods: This is a prospective and comparative study from September 2013 to August 2014 involved 100 cases, 50 open and 50 lap appendicectomy, which were randomly selected and were operated in department of surgery, Dr S. M. C. S. I. Medical College, Karakonam. Results: In present study pain score was 2.7±0.9 for open group as compared to 1.3±0.5 in lap group (P<0.05) because of longer incision stretch of muscles and wound infection. Post operative complications like vomiting was lower in laparoscopic group with 8% as compared with 36% in open group (P<0.05) and ileus was lower in lap group with 17.3±7.1 and for open group 30.8±8.9 with P<0.05 which were significant. There is significant reduction in incidence of post operative wound infection in lap group 4% as compared to open group 26% (P<0.05). Duration of post operative hospital stay was significantly low for lap group 2.8±0.9 as compared to open group 4±2.9. The return to normal activity was low for lap group 8±3.15 days as compared to open group 13.7±3.15 days. Duration of surgery for open appendicectomy was 48.2±12.4 and for lap appendicectomy was 68.5±20.3. Conclusions: Laparoscopic appendicectomy is better than open appendectomy in selected patients with acute or recurrent appendicitis.